Analysis of the repercussions of the war between Israel and the Palestinian resistance on the Middle East - NoorAlDeen Fadhel Mlaghi (Thi Qar Arts Journal, 2025)
This study aims to analyze the consequences of the war between Israel and the Palestinian resistance from military, economic, and humanitarian perspectives. The Middle East continues to witness ongoing conflicts that affect its political and economic stability. The study reviews both the direct and indirect causes that led to the outbreak of the war, considering the Israeli-Palestinian conflict as one of the key factors reshaping the balance of power in the region. With the eruption of the latest war, numerous repercussions have emerged, impacting various regional and international actors. These developments raise questions about the medium- and long-term effects of the conflict. The study also examines the economic consequences of the war, including the damage to Gaza’s infrastructure and its impact on global energy markets and trade. The research traces the implications of this war, which has become one of the longest and most complex conflicts of the modern era. Politically, the study highlights how the war has deepened divisions within both Israeli and Palestinian societies. On the humanitarian level, the research exposes the catastrophe endured by civilians, particularly in Gaza, including the destruction of vital infrastructure and facilities, internal displacement, rising unemployment, and the collapse of both the healthcare and education systems. Statistics indicate that Israeli airstrikes have resulted in the death and injury of thousands of women and children, prompting widespread international criticism. Economically, the ongoing conflict has directly affected both the Israeli economy and the Gaza Strip. Regionally, the study shows that the war has contributed to reshaping alliances in the Middle East. While some countries expressed humanitarian support for Palestinians, their political stances remained cautious, revealing a clear disparity between official and popular positions. The study concludes that the conflict deepens instability in the region, fuels public anger, and makes prospects for peace increasingly complex—unless urgent and effective international intervention is undertaken to stop the war and the ongoing cycle of violence against civilians.